Chronic Intermittent Hypoxia Differentially Impacts Different States of Inspiratory Activity at the Level of the preBötzinger Complex - Garcia, Alfredo J.; Dashevskiy, Tatiana; Khuu, Maggie A.; Ramirez, Jan-Marino (Frontiers in Physiology, 2017)
The preBötzinger complex (preBötC) is a medullary brainstem network crucially involved in the generation of different inspiratory rhythms. In the isolated brainstem slice, the preBötC reconfigures to produce different rhythms that we refer to as “fictive eupnea” under baseline conditions (i.e., carbogen), and “fictive gasping” in hypoxia. We recently demonstrated that fictive eupnea is irregular following exposure to chronic intermittent hypoxia (CIH). However, it is unknown how CIH impacts fictive gasping. To address this, brain slices containing the preBötC were prepared from control and CIH exposed mice. Electrophysiological recordings of rhythmogenesis were obtained during the perihypoxic interval. We examined how CIH affects various dynamic aspects of the rhythm characterized by: (1) the irregularity score (IrS), to assess burst-to-variability; (2) the fluctuation value (χ), to quantify the gain of oscillations throughout the time series; and (3) Sample Entropy (sENT), to characterize the pattern/structure of oscillations in the time series. In baseline conditions, CIH increased IrS of amplitude (0.21 ± 0.2) and χ of amplitude (0.34 ± 0.02) but did not affect sENT of amplitude. This indicated that CIH increased burst-to-burst irregularity and the gain of amplitude fluctuations but did not affect the overall pattern/structure of amplitude oscillations. During the transition to hypoxia, 33% of control rhythms whereas 64% of CIH-exposed rhythms showed no doubling of period, suggesting that the probability for stable rhythmogenesis during the transition to hypoxia was greater following CIH. While 29% of control rhythms maintained rhythmicity throughout hypoxia, all slices from CIH exposed mice exhibited rhythms throughout the hypoxic interval. During hypoxia, differences in χ for amplitude were no longer observed between groups. To test the contribution of the persistent sodium current, we examined how riluzole influenced rhythmogenesis following CIH. In networks exposed to CIH, riluzole reduced the IrS of amplitude (-24 ± 14%) yet increased IrS of period (+49 ± 17%). Our data indicate that CIH affects the preBötC, in a manner dependent on the state of the oxygenation. Along with known changes that CIH has on peripheral sensory organs, the effects of CIH on the preBötC may have important implications for sleep apnea, a condition characterized by rapid transitions between normoxia and hypoxia.